Awareness of Rural People about Prevention of Non-Communicable Diseases - Alam, Md Entekhab Ul; Amin, Md Nurul; Haque, Md Jawadul; Hasan, Farzana; Haldar, Milon Kumar; Yasmin, Nelofar; Shah Amanath Ullah, Shathi Kumar Rawson Kamal Md. Abu Syem; Yasmin, Farhana; Arefin, Md Maruful; Islam, Shitil Ibna; et al. (Ibrahim Cardiac Medical Journal, 2021)
Background & Objective: Non-communicable diseases, particularly diabetes, hypertension and ischemic heart diseases have created an epidemic situation worldwide. Bangladesh is also in the grip of the menace. The only way to get rid of the menace is prevention of these diseases which demands awareness against the diseases. This study was undertaken to assess the level of knowledge of adult people of Puthia Upazila regarding prevention of the seclected non-communicable diseases (NCDs). Methods: The study was carried out in the Department of Community Medicine Rajshahi Medical College, Rajshahi over a period of 2 months from April 2018 to May 2018. All adult people (18 years onwards) residing in the rural area of Puthia Upazila were the respondents (study population) in this study. The survey invited the adult individuals to participate in the study. A total of 1001 individuals voluntarily responded to participate in the study. Of them 648(64.7%) were free from the NCDs and were interviewed to assess their level of knowledge on prevention of selected NCDs. A self-administered questionnaire containing the variables of interest for evaluating knowledge was used. Result: Two-thirds (68.2%) of the respondents were 30–50 years old with mean age of the respondents being 44.3(range: 25-90) years. Males outnumbered females by 11:9. Over half (54%) informed that they had little knowledge and 10.7% were familiar with the NCDs. Around half held the view that diabetes, hypertension, ischemic heart diseases and stroke were NCDs/chronic diseases. Approximately 70% told that the NCDs were on a rising trend. Regarding causes of chronic diseases, the respondents told excess intake of fat and sedentary life-style (67.9%), intake of excess CHO (54.2%), indulgence in smoking (68.2%), less intake of vegetables and fruits (57.4%), excess or additional salt intake (50.5%) and family history of NCD (44.1%). Regarding prevention of NCDs, around 70% were in favor of adopting healthy dietary behaviour and avoiding too much fatty food, followed by regular exercise (71.2%), avoiding or giving up smoking (70.8%) and avoiding or giving up taking extra salt (57.9%). Conclusion: The study concluded that the people of Puthia Upazilla are aware more or less about the selected NCDs (diabetes, hypertension, ischemic heart diseases and stroke). They are also aware that these diseases are increasing. Around two-thirds of the people are aware about the risk factors of these non-communicable diseases and the ways to prevent them. Ibrahim Card Med J 2020; 10 (1&2): 27-32